2015
DOI: 10.1007/s00438-015-1099-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants in INS (rs689), INSR (rs1799816) and PP1G.G (rs1799999) with type 2 diabetes (T2D): a case–control study in three ethnic groups from North-West India

Abstract: Genetic contributions towards Type 2 diabetes (T2D) have been assessed through association studies across different world populations with inconsistencies. The majority of the T2D susceptibility loci are common across different races or populations but show ethnicity-specific differences. The pathogenesis of T2D involves genetic variants in the candidate genes. The interactions between the genes involved in insulin signaling and secretory pathways are believed to play an important role in determining an indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…The Asp/Tyr missense variant of SNP rs1799999 in the PP1RR3A gene, which previously has been shown to associate with T2D risk in Jat Sikhs , showed a trend towards association in Indian women ( P = 0.06; Table ). The variant was also nominally associated with decreased 2‐hour (2‐h) insulin in Swedish women ( P = 0.02, Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Asp/Tyr missense variant of SNP rs1799999 in the PP1RR3A gene, which previously has been shown to associate with T2D risk in Jat Sikhs , showed a trend towards association in Indian women ( P = 0.06; Table ). The variant was also nominally associated with decreased 2‐hour (2‐h) insulin in Swedish women ( P = 0.02, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, 6 loci have been associated with T2D or GDM in India [11,[16][17][18]. Of them, the rs7178572 SNP near the HMG20A gene was associated with GDM in Indian but not in Swedish women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from frozen and stored buffy coats using (QIAGEN Autopure LS kits. Six SNPs previously associated with GDM or T2D in India [ 21 , 22 , 26 , 27 , 30 ] (Additional file 2 : Table S1) and 79 SNPs previously associated with T2D in Europe and elsewhere from GWAS studies up to 2012 (some of these also with GDM risk from candidate gene studies in GDM populations) were genotyped in the present study (Additional file 2 : Table S1) [ 14 ] on a Sequenom Mass ARRAY Platform (Sequenom San Diego, CA, USA) PLEX using MALDI-TOF mass spectrometer [ 31 ] or Taqman allelic discrimination assays using an ABI Prism 7900 sequence detection system (Applied Biosystems, Foster City, CA, USA). Genotyping was performed at the Lund University Diabetes Centre, Sweden after obtaining permission from ICMR (dated 21 october 2010 and Office of Drugs Controller General (India)(dated 14/12/2010).…”
Section: Methodsmentioning
confidence: 99%
“…For these possible reasons, rs1799817 G > A polymorphism may be a functional variant for INSR gene. Sokhi et al 28 reported that INS rs689 polymorphism was associted with an increased risk of T2D. In addition, Lempainen et al 29 found that this polymorphism, cooperated with PTPN22 rs2476601 and IFIH1 rs1990760 loci, might be correlated with the β-cell autoantibodies.…”
Section: Discussionmentioning
confidence: 99%